Pengaruh Nilai Kurs dan Tingkat Suku Bunga terhadap Dana Pihak Ketiga pada Bank Devisa di Indonesia Tahun 2010-2014 - Dimas Yan Saputra; Gunistiyo (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2016)
The purpose of this study was to 1) to analyze the influence of return on assets (ROA) on stock returns 2) to analyze the influence of return on equity (ROE) to stock return 3) To analyze the effect of the current ratio (CR) on stock returns 4 ) to analyze the effect of the debt to equity ratio (DER) on stock returns and 5) to analyze the influence of return on assets (ROA), return on equity (ROE) current ratio (CR) and a debt to equity ratio (DER) together on stock returns. Data collection method used in this study is documentation. While the data analysis method used is the classic assumption test, multiple regression analysis, partial testing, simultaneous testing and coefficient of determination. Research shows that a significant difference between the return on assets on stock returns. This is evidenced from the results of testing at test obtained significant results. A significant difference between the return on equity on stock returns. This is evidenced from the results of the test results at test obtained significant results. A significant difference between the current ratio on stock returns. This is evidenced from the results of the test results at test obtained significant results. There is no significant relationship between debt to equity ratio on stock returns. This is evidenced from the results of the test results at test obtained significant results. A significant difference between the ROA, ROE, CR and DER to stock return. This is evidenced from the test results obtained F test probability value obtained significant results. From the calculation of unknown value determination coefficient of 0.658 means that return on assets (ROA) and return on equity (ROE) influence or contribute jointly to the stock return is affected by other factors that can not be explained.